2012
DOI: 10.1007/s10545-012-9464-3
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of BH4 before the age of 4 years in patients with mild phenylketonuria

Abstract: BH4-therapy is efficient and safe before the age of 4 years in mild PKU, BH4-responsive patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 26 publications
(30 reference statements)
3
17
0
Order By: Relevance
“…Previous studies have indicated that sapropterin improves blood Phe control while clinically requiring dietary Phe adjustments, leading to less restrictive diets and, in some cases, discontinuation of Phe-free medical food. 25,26,28,29 The current study confirms and extends this observation to younger children who have a higher growth velocity and, consequently, a relatively higher requirement for phenylalanine.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies have indicated that sapropterin improves blood Phe control while clinically requiring dietary Phe adjustments, leading to less restrictive diets and, in some cases, discontinuation of Phe-free medical food. 25,26,28,29 The current study confirms and extends this observation to younger children who have a higher growth velocity and, consequently, a relatively higher requirement for phenylalanine.…”
Section: Discussionsupporting
confidence: 84%
“…[22][23][24][25] In a recent study of 15 children younger than age 4 years with PKU, sapropterin improved blood Phe control while clinically requiring dietary Phe adjustments, allowing increased intact protein intakes; however, the impact of sapropterin on neurocognitive development was not assessed. 26 A retrospective analysis of children and adults with BH4-responsive PKU demonstrated that the improved metabolic control and dietary adjustments associated with sapropterin therapy were maintained long term (up to 12 years). 27 This study was conducted to prospectively evaluate the longterm efficacy of sapropterin in preserving neurocognitive function in children with PKU who began sapropterin treatment between 0 and 6 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 25-50% of the patients with PAH deficiency are sapropterin-responsive. 19,[35][36][37] Patients with mild PAH deficiency are most likely to respond because some stable protein is required for sapropterin to function; nonetheless, responsive patients are identified even among those with complete PAH deficiency. Genotype may be predictive of sapropterin response, but genotype-phenotype correlations thus far are imperfect.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…16 Sapropterin has been used under the age of 4 years in PAH deficiency and in patients with biopterin synthesis defects. 36,40 Sapropterin responsiveness is commonly determined by obtaining a baseline blood PHE level on the day the medication is initiated (baseline) and then starting the patient on a single daily dose of sapropterin at 20 mg/kg. Additional blood PHE levels are then obtained at regular intervals, usually at 24 h, 1 week, 2 weeks, and in some cases, 3 or 4 weeks.…”
Section: Pharmacotherapymentioning
confidence: 99%
“…Common measures are the percentage of decrease in blood Phe from a baseline level over 24 to 48 h; this decrease varies widely [5][6][7][8][9][10]. Two proposals on how to perform this test have been made [11,12] and a large series of reports involving patients of different ages has shown that response varies, depending on dosing, duration of loading, preloading with Phe genotype and severity of the enzyme defect [13].…”
Section: Introductionmentioning
confidence: 99%